Wheat Cost-Return Budget in Southeast Kansas - Fogleman, Sarah L.; Kilgore, Gary L. (My University, 2007)
This publication outlines the expected costs and returns for wheat in southeast Kansas.
MF992_2007_10
Keywords: MF992; Economics; Crops; MF